Analysis of patron-client political communication in building a network of political power in the village community - Suyono, Suyono; Nugroho, Kris; Windyastuti, Dwi (Jurnal Studi Komunikasi, 2021)
This study aimed to explore political communication in the building of political power networks in Jenggrik Village, Kedunggalar District, Ngawi Regency during the village head elections (village head election) from 1998 to 2019 from patron-client relations perspective. Political communication occurs through village elites and village community leaders. Political communication happens between the village head and his community members. This study was a descriptive study using a qualitative research method. This study sought to understand the processes and facts about political communication that shapes community loyalty and the leaders in Jenggrik Village, Kedunggalar District who have economic and non-economic power. The findings and conclusions of this study supported Max Weber's notion on Charismatic Leadership as well as Sartono Kartodirjo’s research which stated that the loyalty of village communities (clients) is formed because of village heads (patrons) for material (economic) and non-material (non-economic) reasons, such as authority and charisma of the leader; distribution of benefits from individuals or groups in exchange for political support; the loyalty of village communities, according to Jonathan Hopkins; also material factors such as financial aid, village physical infrastructure development assistance, or other economic assistance, according to James C. Scott and Ahimsa.